(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
Electronic environment offers new possibilities for publishing research results in scientific journals – linking to other digital documents; connecting documents with their newer (or older) versions; publishing video/audio recordings, high resolution photos or 3D models; publishing in open access; controlling quality by open peer-review, etc. The results of research on Croatian scientific journals (from all scientific fields, all published in open access on Hrčak, the central portal of Croatian scientific journals) show that all journals, except one, publish articles as PDF files. Approximately one fourth of the journals use automated publishing systems. Majority of the journals publish active links to authors’ e-mail addresses and some of them publish active links to online sources in the reference lists. Linking higher resolution photographs, tables or charts is not common practice in Croatian journals. In spite of the significant number of Croatian scientific electronic journals, their content is still static, not enriched by various possibilities offered by new technologies.